Pengaruh Harga, Promosi Penjualan dan Store Atmosphere Terhadap Kepuasan Konsumen pada Starbucks Coffee Mall Of Indonesia - Saphira Tuffahati; Mariah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of prices, sales promotion and store atmosphere on consumer satisfaction at Starbucks Coffee Mall of Indonesia in May 2019. The research was proven by a series of quantitative methods using the SPSS application. There are 100 respondents selected data based on the experience of consumers who have made a purchase transaction at least twice. The results show prices, sales promotions and store atmosphere affect consumer satisfaction. The accepted hypothesis was decided based on t value analysis. So based on the research findings, Starbucks Coffee Mall of Indonesia must increase the comfort of consumers and provide prices in accordance with the quality in order to create satisfaction for consumers.